Dissensus and Poetry: The Poet as Activist in Experimental English-Canadian Poetry - Leduc, Natalie (Université d'Ottawa / University of Ottawa, 2019)
Many of us believe that poetry, specifically activist and experimental poetry, is capable of intervening in our society, as though the right words will call people to action, give the voiceless a voice, and reorder the systems that perpetuate oppression, even if there are few examples of such instances. Nevertheless, my project looks at these very moments, when poetry alters the fabric of our real, to explore the ways these poetical interventions are, in effect, instances of what I have come to call “dissensual” poetry. Using Jacques Rancière’s concept of dissensus and the distribution of the sensible, my project investigates the ways in which dissensual poetry ruptures the distribution of the sensible—“our definite configurations of what is given as our real, as the object of our perceptions and the field of our interventions”—to look at the ways poetry actually does politics (Dissensus 156). I look at three different types of dissensual poetry: concrete poetry, sound poetry, and instapoetry. I argue that these poetic practices prompt a reordering of our society, of what is countable and unaccountable, and of how bodies, capacities, and systems operate. They allow for those whom Rancière calls the anonymous, and whom we might call the oppressed or marginalized, to become known. I argue that bpNichol’s, Judith Copithorne’s, and Steve McCaffery’s concrete poems; the Four Horsemen’s, Penn Kemp’s, and Christian Bök’s sound poems; and rupi kaur’s instapoems are examples of dissensual poetry.
Keywords: Canadian literature; Canadian poetry; Experimental poetry; Concrete poetry; Visual poetry; Sound poetry; Instagram poetry; Instapoetry; bpNichol; Steve McCaffery; Judith Copithorne; The Four Horsemen; Penn Kemp; Christian Bök; rupi kaur; instapoet; Stephen Collis; Sina Queyras; Jacques Rancière; Dissensus; Activism; Activist; Walter Benjamin; Michael Warner